The Role of Educational Technology in Improving Access in Rural Areas: A Case Study of YPPK ST. Petrus Yarat Konya Maybrat Regency - Funan, Forita (Riwayat: Educational Journal of History and Humanities, 2024)
The research examines the roleof educational technology in increasing access to education in rural areas, especially in Yppk St Peters Elementary School in Konya Maybrat Regency as a case study. Rural areas often face challenges in accessing quality education, mainly due to long geographical distances and limited infrastructure. Educational technology has become an important tool in overcoming these obstacles. Through the use of distance learning, access to information, online teacher training, and improved communication, educational technology has enabled students in Maybrat Country to access better education. The use of mobile devices also provides additional flexibility in the teaching-learning process. The research illustrates how the application of educational technology has contributed to the improvement of access to education in rural areas and provides insights that can be used as a reference for similar efforts in similar areas. The results show that education technology has great potential in expanding the scope of education in rural areas such as Maybrat Country and enabling continuous improvement in the quality of education there. Here, almost all parents are able to send their children to school. The obstacle in this globalization era, namely the application or use of ICT-based learning media, is still experiencing limitations because of its geographical reach, the provision of infrastructure facilities and the need for quality improvement for teachers through training, mentoring, control from related agencies and continuous evaluation